2017
DOI: 10.4038/cjs.v46i4.7470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 18 isolates of basidiomycetes for Lignocellulose degrading enzymes

Abstract: Since fossil fuel resources are limited there is a necessity to produce alternative types of fuel that are renewable and eco-friendly. Basidiomycetes are potential sources of enzymes that can be used for biofuel production. The current study aimed to isolate basidiomycetes from Sri Lanka, screen them for lignocellulose degrading enzymes, namely cellulase, xylanase, laccase, Mn peroxidase and lignin peroxidase and study the effect of potential inducers of laccase production. Among the eighteen basidiomycetes is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
2
7
0
1
Order By: Relevance
“…As per the results, E. scabrosa was the most efficient fungal isolate in pretreatment of sugarcane bagasse by performing delignification. In a previous study, the same E. scabrosa isolate showed 0.00912 U/mL laccase activity in glucose containing medium (Kathirgamanathan et al, (2017). The current study confirmed that the addition of sugarcane bagasse has induced the laccase activity of the isolate.…”
Section: Sugarcane Bagasse Pretreatment Potential Of Fungal Isolatessupporting
confidence: 87%
See 2 more Smart Citations
“…As per the results, E. scabrosa was the most efficient fungal isolate in pretreatment of sugarcane bagasse by performing delignification. In a previous study, the same E. scabrosa isolate showed 0.00912 U/mL laccase activity in glucose containing medium (Kathirgamanathan et al, (2017). The current study confirmed that the addition of sugarcane bagasse has induced the laccase activity of the isolate.…”
Section: Sugarcane Bagasse Pretreatment Potential Of Fungal Isolatessupporting
confidence: 87%
“…Ten fungal isolates were evaluated in the current study for their sugarcane bagasse pretreatment and saccharification potential. As previously mentioned, two efficient ligninolytic basidiomycete isolates: E. scabrosa and T. hirsuta (Kathirgamanathan et al, 2017) and eight efficient cellulolytic filamentous fungal isolates which belonged to three main genera, viz. Aspergillus, Trichoderma and Penicillium (Jayasekara et al, 2020) were evaluated.…”
Section: Selection Of Fungal Isolatesmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the three groups of bacteria, namely, actinomycetes, α-proteobacteria, and γ-proteobacteria, are known to have ligninolytic systems. Some actinomycetes were studied for their role in lignin biodegradation [37]. These degraded lignin into low-molecular-weight fragments.…”
Section: Microorganisms Employed In Biological Pretreatmentmentioning
confidence: 99%
“…In a different study, 18 basidiomycete isolates from the natural environment of Sri Lanka has been evaluated for their lignocellulose-degrading enzyme production. An Earliella scabrosa species with higher laccase activity (79,600 U/l) when cultured in 50 g/l rice bran has been reported [37]. Thus, it can potentially be used for industrial production of laccase using rice bran as a cheap carbon source for high laccase production.…”
Section: Enhancement Of Biological Pretreatment Efficiencymentioning
confidence: 99%